Número de subamostras e variabilidade espacial de atributos químicos do solo em sistema plantio direto - Oliveira, Douglas Machado (2017)
The fundamental step of a fertility assessment program is soil sampling, in which the number of points collected should be sufficient to detect the spatial variability of soil attributes. However, due to soil heterogeneity, there is no agreement on the number of subsamples needed to estimate the soil properties values, with sufficient precision and representativeness. Therefore, the objective of this work is to determine the spatial variability of soil chemical attributes in areas under no-tillage system with fertilization in the line and the haul, and to establish the minimum number of subsamples necessary to form a representative composite sample within certain precision limits . The work was carried out in two properties, located in the municipality of Palmeira das Missões - RS. Soil sampling was performed at points of intersection in a square mesh of 49 points, spaced at regular intervals of 5 x 5m. The samples were collected in two different management systems, one area under no-tillage with fertilization in the line and the other with fertilization in the haul. In both areas, the soil was collected with a shovel in the 0-0.15 m depth. The evaluated attributes were: pH, P, K, Ca, Mg, H + Al, CTC, V% and MO. The data were submitted to the exploratory analysis, and the statistical parameters determined were: mean, median, minimum, maximum, standard deviation, coefficients of variation, asymmetry and kurtosis. The minimum number of subsamples required to form a representative composite sample was also determined. The ideal number of subsamples, to form a representative composite sample, will vary according to the fertilization system, error probability and error in relation to the mean. Among the precision limits studied, it was recommended to work both in the system with fertilization in the haul and in the line with probability of error α of 0.05 and error in relation to the average of 20%. Considering this same error, it is suggested to collect at least 11 to 12 subsamples per sample point, to form a representative composite sample with a cutting blade.